Middle Neolithic pits and a burial at West Amesbury, Wiltshire. Issue 2 (2nd July 2020) - Roberts, David; Barclay, Alistair; Bishop, Barry; Bronk-Ramsey, Christopher; Campbell, Greg; Canti, Matthew; Dobie, Judith; Dunbar, Elaine; Dunne, Julie; Evershed, Richard P.; Forward, Alice; Last, Jonathan; et al.
ABSTRACT: Excavations on the south-eastern slopes of King Barrow Ridge, 1.5 km east of Stonehenge, revealed five pits, a grave and other features of Middle Neolithic date. Analysis of the pit assemblages and the partial inhumation interred in the grave has provided insights into lifeways in this landscape in the late fourth millennium cal BC. Evidence suggests that the area was visited by a pastoralist, mobile community on a semi-regular basis for a significant period, in late autumn or winter. Selected remnants of craft-working and consumption were deposited in pits, before deliberate infilling. These depositions repeatedly memorialised activity on the hillside at a time of contemporary activity elsewhere on King Barrow Ridge and at the future site of Stonehenge. Middle Neolithic pits are present in significant numbers across King Barrow Ridge, and alongside pits in the Durrington area, form one of the densest concentrations of such activity in the region. Long distance mobility is suggested by the possible Irish origins of the inhumation, the first Middle Neolithic individual excavated in the environs of Stonehenge. Whilst of significance for understanding the Middle Neolithic in the WHS and the region, this research also hints at the roots of Late Neolithic monumentalisation of this landscape.